2016
DOI: 10.1097/mib.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Disease Course and Colectomy Rate of Ulcerative Colitis

Abstract: The colectomy rate was low in our cohort and further reduced in the last 2 decades. However, despite the availability of anti-TNFα agents, no further significant reduction of colectomies was observed in the last decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Some studies have also examined risk factors for colectomy in these populations [16, 109, 122, 131–133]. As expected, the extent of colitis and flare duration are associated with increased risk of colectomy.…”
Section: Ulcerative Colitismentioning
confidence: 90%
See 1 more Smart Citation
“…Some studies have also examined risk factors for colectomy in these populations [16, 109, 122, 131–133]. As expected, the extent of colitis and flare duration are associated with increased risk of colectomy.…”
Section: Ulcerative Colitismentioning
confidence: 90%
“…Between 10% and 30% of UC patients will ultimately require a colectomy [4, 22, 109]. Patients undergo total abdominal colectomy, proctocolectomy or, in rare cases, partial colectomy for the management of dysplasia or cancer, medication intolerance or, in the vast majority (∼90%) of cases, for medically refractory disease [110].…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…Of note, our reported colectomy rate was 18% in patients with UC, which mirrors the incidence reported in single-center studies, but is lower than that observed in population-based cohorts and prospective multi-center registries of UC alone. 3436 …”
Section: Discussionmentioning
confidence: 99%
“…15 International studies reported colectomies in 7%-10% of patients with UC, with decreasing colectomy rates over recent years. [16][17][18] Active UC is associated with reduced health-related quality of life (HRQoL) and productivity, [19][20][21][22][23][24] frequent visits to accident and emergency departments (A&E), hospital stays and healthcare costs, [24][25][26] with greater costs with increasing frequency of relapse. 27 Although colectomy may be life-saving, it was recommended not to be considered a cure for UC.…”
Section: Key Messagesmentioning
confidence: 99%